Book review: Ethnographies of academic writing research: Theory, methods, and interpretation - Bowen, Neil (Journal of Writing Research, 2022)
Book review of Guillén-Galve, I. & Bocanegra-Valle, A. (Eds.) (2021). Ethnographies of academic writing research: Theory, methods, and interpretation. Amsterdam, The Netherlands: John Benjamins Publishing Company | 162 pages ISBN: 9789027210067 | <a href="Guillén-Galve,%20I. & Bocanegra-Valle, A. (Eds.) (2021). Ethnographies of academic writing research: Theory, methods, and interpretation. Amsterdam, The Netherlands: John Benjamins Publishing Company | 162 pages ISBN: 9789027210067 | https://doi.org/10.1075/rmal.1">https://doi.org/10.1075/rmal.1